The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.17221/172/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Quality of wheat germ oil obtained by cold pressing and supercritical carbon dioxide extraction

Abstract: Laboratory-prepared wheat germ oil was obtained by cold pressing and supercritical CO 2 extraction. The main objective was to compare the quality of both oil samples obtained, with emphasis on their fatty acids compositions and tocopherol contents. The percentages of palmitic, oleic, linoleic, and linolenic acids determined in the cold-pressed oil were 15.89, 15.48, 54.88, and 7.34% of total fatty acids, respectively, and those in the oil extracted by supercritical CO 2 were 16.50, 15.05, 54.79, and 7.29% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…The results show that the addition of ethanol to the supercritical CO 2 did not affect the fatty acid composition of the whole collected extract (SFE-K compared with SFE-KE). It can also be noted that the total concentrations of the three groups of fatty acids in the extracted oil were similar to those obtained by other investigators (Gomez et al, 2000;Jiang et al, 2011;Özcan et al, 2013;Eisenmenger and Dunford, 2008).…”
Section: Fatty Acid Compositionsupporting
confidence: 89%
“…The results show that the addition of ethanol to the supercritical CO 2 did not affect the fatty acid composition of the whole collected extract (SFE-K compared with SFE-KE). It can also be noted that the total concentrations of the three groups of fatty acids in the extracted oil were similar to those obtained by other investigators (Gomez et al, 2000;Jiang et al, 2011;Özcan et al, 2013;Eisenmenger and Dunford, 2008).…”
Section: Fatty Acid Compositionsupporting
confidence: 89%
“…In a study , it was observed that WGO contains 56.5% linoleic acid, 20.0% palmitic acid, and 14.7% oleic acid in WGO. Özcan et al evaluated quality of WGO obtained by cold pressing and supercritical carbon dioxide extraction and found that the percentages of palmitic, oleic, linoleic, and linolenic acids were 15.89, 15.48, 54.88, and 7.34% of total fatty acids (cold pressed oil) and 16.50, 15.05, 54.79, and 7.29% of fatty acids (supercritical carbon dioxide extracted oil), respectively. The percentages of saturated, mono and polyunsaturated fatty acids were 17.15, 17.63, and 62.22% of total fatty acids in the cold‐pressed oils, but the proportions of those in oils extracted by supercritical carbon dioxide were 18.14, 17.58, and 62.08%, respectively.…”
Section: The Characteristics Composition and Bioactive Contents Of mentioning
confidence: 99%
“…The solvents used for WGO extraction are hexane, 1, 2‐dichloroethane, and ethanol. The catabolism of nutritionally important components of WGO can be minimized by avoiding higher extraction temperatures and by using techniques such as cold pressing and supercritical carbon dioxide assisted extraction . These techniques either avoid or reduce the use of extraction temperature that might be detrimental of heat sensitive nutrients .…”
Section: Extraction Of Wheat Germ Oilmentioning
confidence: 99%
See 2 more Smart Citations